Fundamentals of curriculum : passion and professionalism - Walker, Decker F. (L. Erlbaum Associates, 2003)
Graduate students and teachers of introductory graduate courses in curriculum have many textbooks to choose from. What is special about Fundamentals of Curriculum: Passion and Professionalism, Second Edition? Content and approach: Clear, focused, and tightly structured, this text provides essential information and resources education professionals need to effectively deal with the urgent and important curriculum problems they face in schools today. Part I (""Perspectives"") looks at curriculum from five fundamental perspectives: curriculum work, traditions of curriculum.